Respon kecemasan orang tua terhadap hospitalisasi anak Di RSUP Dr. M.Djamil Padang: Parents' anxiety response to child hospitalization at Dr. M. Djamil Hospital. M.Djamil Padang - Hermalinda; Deswita; Rika Sarfika (Fakultas Keperawatan Universitas Andalas, 2018)
Hospitalization is a stressful experience for both children and their family. This will influence the effectiveness of treatment that is conducted on children and has an impact on the healing process of children. This research aimed to identify the anxiety responses of parents over the hospitalization of children. The design was descriptive analytic with cross-sectional study approach. This research was carried out in pediatrics wards of DR. M.Djamil Hospital from June to October 2018. A total of 133 parents/caregivers participated in this research. Data were collected using the Short STAI (State-Trait Anxiety Inventory) questionnaire and a questionnaire about factors that related to parents' anxiety. Data were analyzed by using the Kruskal Wallis and Mann Whitney test. The results showed that the parents' anxiety score was 18.02 with a standard deviation of 3.69., the lowest score was 7 and the highest was 24. There was a relationship between the duration of stay, previous treatment experience, and condition of children with parents' anxiety. It is expected that nurses can identify stress or parents anxiety by conducting a comprehensive assessment.